2008
DOI: 10.5735/086.045.0509
|View full text |Cite
|
Sign up to set email alerts
|

Inference of Ecological Interaction Networks

Abstract: The inference of the interactions between organisms in an ecosystem from observational data is an important problem in ecology. This paper presents a mathematical inference method, originally developed for the inference of biochemical networks in molecular biology, adapted for the inference of networks of ecological interactions. The method is applied to a network of invertebrate families (taxa) in a rice field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The abundance of large predators and other mammals is similar to that observed in other high latitude areas like Beringia, where Fox- Dobbs et al (2008) reported 5 predators and 6 large potential prey for a wider time span (50e10 ka), or 6 potential large mammalian prey for the period 18e10 ka BP (Guthrie, 2006; see also ;Harington, 2011). A similar situation was present in the Late Pleistocene "Mammoth Steppe Fauna" of northern Eurasia (see Vereshchagin and Baryshnikov, 1992). The comparison with other assemblages of the Late Pleistocene of South America was more difficult, because most of them lacked robust chronological data (there were very few taxon dates) and taphonomic control.…”
Section: Diversity and Temporal Distributionsupporting
confidence: 78%
“…The abundance of large predators and other mammals is similar to that observed in other high latitude areas like Beringia, where Fox- Dobbs et al (2008) reported 5 predators and 6 large potential prey for a wider time span (50e10 ka), or 6 potential large mammalian prey for the period 18e10 ka BP (Guthrie, 2006; see also ;Harington, 2011). A similar situation was present in the Late Pleistocene "Mammoth Steppe Fauna" of northern Eurasia (see Vereshchagin and Baryshnikov, 1992). The comparison with other assemblages of the Late Pleistocene of South America was more difficult, because most of them lacked robust chronological data (there were very few taxon dates) and taphonomic control.…”
Section: Diversity and Temporal Distributionsupporting
confidence: 78%
“…The interaction network is a generic modelling construct that is commonly used in the broader domain of ecology to visualise various kinds of relationships between interacting species. Different ways of inferring specific plant-animal interaction networks from data appear in the literature, including mathematical techniques using symbolic computation and algebraic combinatorics [8], statistical techniques, including correlation analysis [9], hierarchical Bayesian models [10] and Bayesian networks [11,12], and computational methods, including machine learning [13] and network theory [14].…”
Section: Literature Review and Backgroundmentioning
confidence: 99%